Genetic relationships of European, Mediterranean, and SW Asian populations using a panel of 55 AISNPs - Pakstis, Andrew J.; Gurkan, Cemal; Dogan, Mustafa; Balkaya, Hasan Emin; Dogan, Serkan; Neophytou, Pavlos I.; Kidd, Kenneth K. (Springernature, 2019)
The set of 55 ancestry informative SNPs (AISNPs) originally developed by the Kidd Lab has been studied on a large number of populations and continues to be applied to new population samples. The existing reference database of population samples allows the relationships of new population samples to be inferred on a global level. Analyses show that these autosomal markers constitute one of the better panels of AISNPs. Continuing to build this reference database enhances its value. Because more than half of the 25 ethnic groups recently studied with these AISNPs are from Southwest Asia and the Mediterranean region, we present here various analyses focused on populations from these regions along with selected reference populations from nearby regions where genotype data are available. Many of these ethnic groups have not been previously studied for forensic markers. Data on populations from other world regions have also been added to the database but are not included in these focused analyses. The new population samples added to ALFRED and FROG-kb increase the total to 164 population samples that have been studied for all 55 AISNPs.
Keywords: Id Ancestry Panel; Snps; Inference; Markers; Origin